Enabling trade across borders and food security in Africa - Isaac Bonuedi; Kofi Kamasa; Eric Evans Osei Opoku (Food Security, 2020)
Widespread food insecurity remains a daunting challenge in Africa, despite significant gains in global efforts to eliminate hunger over the last three decades. This paper examines the effects of easing trade across borders – through reductions in documents, time, and costs to export and import – on food security outcomes in Africa. To control for endogeneity, this paper employs the first-difference instrumental variable estimator based on panel data covering 45 African countries over the period 2006–2015. The results reveal that poor trade facilitation constitutes a significant driver of food insecurity in Africa. In particular, ineffective trade facilitation is associated with significant increments in the prevalence of undernourishment and depth of food deficit, as well as reductions in dietary energy supply adequacy and access to sanitation facilities. The results show that food availability and food access are significantly hampered by higher documentation requirements and lengthier export and import times. The results suggest that reductions in delays from documentary and border compliance promise to be the most effective trade facilitation reforms to enhance food security in Africa.
Keywords: O24; Q18; F13; C36; 630; Food security; Trade facilitation; First-difference instrumental variable; Africa